Fatigue failures of differences behaviour on CSM/woven roving composite materials - T. Arifin, A.M.; Abdullah, S.; Zulkifli, R.; Wahab, D.A. (Trans Tech Publications, 2014)
This paper presents the investigation of composite materials lamination using different materials in the structure of lamination. The main purpose of the study is to evaluate the behaviour of characteristics in composite materials subjected to difference of fatigue loading, leading to understand the criteria that influence the behaviour of composite lamination structure. Therefore, in this research, the orientation of lamination structure used is 00/900 and the material selected for the study were chopped strand mat (csm) and woven roving fabric (wr) as a reinforcement and the matrix used were polyester and epoxy resin. The composite lamination structure was produced using hand lay-up technique. The fatigue condition experiment of composite materials in this research was carried under tension-tension loading. With difference in fatigue loading condition, the lifetime of composite structure will be different and the cracking phenomenon in the structure will also be different. It is suggested that, different number of lamination and amount of reinforcement and matrix, produce a variety of materials characteristic with respect to elasticity of material. An implication of the study in this research showed various behaviour of composite materials with different materials used and it showed a difference phenomenon in comparison to metalic materials.